The Influence of Principal Leadership and Teacher Teaching Performance on Student Learning Motivation at SD Negeri Gugus VII, Doloksanggul District, Humbang Hasundutan Regency - Simamora, Reli Rita; Gultom, Rogate Artaida Tiarasi; Sihaloho, Martua; Samosir, Lustani; Tarigan, Iwan Setiawan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of Principal Leadership and Teacher Teaching Performance on Student Learning Motivation individually and together. This research used quantitative descriptive inferential methods, with a population of all students at SD Negeri Gugus VII, Doloksanggul District, totaling 177 people, a sample of 45 people. The questionnaire was tested on 30 students outside the research sample, and was tested using validity and reliability tests. The research results show: 1). There is a positive and significant influence of Principal Leadership on Student Learning Motivation of 35.9% with rcount > rtable (0.599 > 0.294) and tcount > ttable (4.912 > 2.021). 2). There is a positive and significant influence of Teacher Teaching Performance on Student Learning Motivation of 38.1% with rcount > rtable (0.617 > 0.294) and tcount > ttable (5.148 > 2.021), 3). There is a positive and significant influence of Principal Leadership and Teacher Teaching Performance together on Student Learning Motivation of 42.1% with Fcount > Ftable (28.874 > 3.23), thus H0 is rejected and Ha is accepted, meaning there is a positive influence and Principal Leadership and Teacher Teaching Performance are significant on Student Learning Motivation at Gugus VII Public Elementary School, Doloksanggul District, Humbang Hasundutan Regency, individually or together because it has been empirically tested. together because it has been empirically tested.